Effect of different feeding system on the performance of crossbred pigs - MURUGAN, M; MATHEW, JOSEPH; SIVAKUMAR, T; GNANARAJ, P TENSINGH (The Indian Journal of Animal Sciences, 2011)
A growth trial was conducted to evaluate the performance of Duroc×(Landrace×desi) pigs under different feeding systems. Weaned piglets (24) were selected at random and they were divided into 4 groups comprising 6 animals each. First group (T1) was maintained on farm concentrate. Piglets belonging to T2, T3 and T4 were fed with swill feed. In addition to this, T3 and T4 group were supplemented with inorganic and organic minerals @ 1% level on dry matter basis respectively. There was no significant difference in monthly body weights, body measurements, ADG and average daily feed intake between T1 and T2. T4 was significantly better than other treatment groups. Feed efficiency was significantly better on T1 and lower on T2, T3 and T4. T4 attained significantly higher slaughter weight, hot carcass weight and carcass length than the other treatment groups. T3 group attained significantly higher slaughter weight, hot carcass weight and carcass length than the T2 and T1 treatment groups. No significant difference between T1 and T2 was noticed. T1 had significantly higher dressing percentage; lesser back fat thickness and gut weight than other treatment groups. There was no significant difference between T2, T3 and T4 in dressing percentage and back fat thickness. T2 had significantly lesser loin eye area and meat-bone ratio than other treatment groups.It was concluded that swill feed was found to be equally effective compared to concentrate feed in promoting growth of the fattener pig production existing under field conditions. Carcass characteristics and growth can be improved by supplementation of minerals in the diet of fattener pigs.